EKSPLORASI NILAI-NILAI TRADISI TUMALI DALAM PERSPEKTIF PENDIDIKAN AGAMA KRISTEN DI DESA RAMBUNAN KABUPATEN MINAHASA - Yolanda Pongoh; Semuel Selanno; Jefri Mailool (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2026)
This study explores the cultural values embodied in the Tumali tradition of Rambunan Village, Minahasa, and their significance for Christian Education. The research problem arises from the need to understand how cultural traditions can serve not only as social mechanisms but also as pedagogical spaces for faith formation. Using a qualitative phenomenological approach, data were collected through in-depth interviews, field observations, and document analysis, then analyzed thematically with triangulation to ensure credibility. The findings reveal that Tumali contains eight interrelated values responsibility, mutual cooperation, love, justice, honesty, care, loyalty, and sacrifice manifested in a reciprocal pattern of “mutuality” (supporting, caring, and serving one another). Anthropologically, Tumali strengthens social cohesion and cultural identity; theologically, it reflects Christian values of agape love, fellowship, and service. In the perspective of Christian Education, Tumali functions as a “school of faith” where young generations experience and internalize gospel values through lived communal practices. This study concludes that Tumali is not only a means of cultural preservation but also a contextual medium for embodying and transmitting Christian faith across generations.